Consumption effects of commercialization of agriculture - Bouis, Howarth E. (International Food Policy Research Institute, 1994)
The commercialization of agricultur has, in many diverse circumstances, led both to an increase in household income and to changes in the way household resources are organized to earn that income, Have these changes meant that food intakes are more nutritions and that health and sanitation conditions are improved? This chapter addresses three central questions: (1) to what extent are increments in income spent on nonfood items, in particular, health-related items; (2) to what extent are increments in income spent on food, and (controlling income) dows the switch to commercial production alter the marginal propensities to spend on food; and (3) to what extent do increments in food expenditures lead to greater calorie intakes, both at the household level and at the individual preschooler level?